Excess deaths from all-causes mortality in children following the discontinuation of the COVID-19 policy in Thailand - Phanthila Sitthikarnkha; Sirapoom Niamsanit; Leelawadee Techasatian; Suchaorn Saengnipanthkul; Rattapon Uppala (BMC Public Health)
Abstract Background The emerging COVID-19 pandemic impacted excess mortality in adults. However, limited information is available about the number of children who died during and after the discontinuation of COVID-19 policies in Thailand. This study aimed to assess the excess mortality in Thai children during and after the discontinuation of COVID-19 policies in Thailand. Method We obtained data on all-cause mortality among children from birth until 15 years of age from the Thai Bureau of Registration Administration (BORA) between January 2015 and December 2023. Based on WHO methodology, the negative binomial distribution model was used to calculate expected mortality. The excess mortality was calculated by taking the difference between the actual all-cause and expected mortality and presented as a P-score. Results There were 81,510 all-cause deaths in children during the study period. Males were more affected than females, accounting for 60.5% of all deaths. Children younger than one year of age had the highest mortality rate (37,069 deaths, 45.5%). Of these, the number of child deaths during and after the COVID-19 pandemic were 20,555 and 9,924, respectively. During the COVID-19 pandemic, the average monthly excess mortality decreased from January 2020 to September 2022 when surveillance measures were in place. However, once the national surveillance measures ended in October 2022, excess mortality experienced a significant increase, with a P-score of 13.0%. The highest monthly average P-score for children aged 3 years, particularly in October 2022. Conclusions The all-cause mortality of children in Thailand during the COVID-19 pandemic was significantly reduced. However, following the pandemic, mortality rates appear to have increased, particularly among children aged 2 to 3 years. It is crucial to investigate the causes of these post-pandemic excess deaths to better prepare for future pandemics.